PERMAINAN OUTBOND KIDS KAHANJAK ATEI SEBAGAI SARANA MELATIH PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI TK AISYIYAH BUSTANUL ATHFAL 1 PALANGKA RAYA - Muzakki; Aghnaita; Neela Afifah; Eka Nurhalisa; Nur Aida; Nadila Raudhatul Aisy (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2022)
Education provided in early childhood at the kindergarten / RA education level is not only fixated on providing material directly and not only always in the classroom, but education can also be done outside the classroom which is designed to provide education through physical activity in a recreational setting, these activities are often known as outbound. The purpose of carrying out Kahanjak Atei outbound kids activities is to provide a fun learning atmosphere, train focus, courage, and further improve social-emotional development and teamwork between students with one another. This research uses the ITGbM method in its implementation using lecture, discussion and practice methods. The implementation of the outbound kids kahanjak atei game was carried out to 25 students of TK Aisyiyah Bustanul Athfal 1 Palangka Raya. There are 5 outbound kids kahanjak atei games in its application, namely: 1) Move the ball according to color, 2) Blow ping pong balls, 3) Paper clip relay, 4) Crown relay, 5) Blow glasses.